RT-PCR–DGGE Analysis to Elucidate the Dominant Bacterial Species of Industrial Spanish-Style Green Table Olive Fermentations - Benítez-Cabello, Antonio; Bautista-Gallego, Joaquín; Garrido-Fernández, Antonio; Rantsiou, Kalliopi; Cocolin, Luca; Jiménez-Díaz, Rufino; Arroyo-López, Francisco N. (Frontiers in Microbiology, 2016)
This paper describes the dominant bacterial species metabolically active through the industrial production of Spanish-style Manzanilla and Gordal olives. For this purpose, samples (brines and fruits) obtained at 0, 15 and 90 fermentation days were analysed by a culture-independent approach to determine viable cells by reverse transcription of RNA and further PCR-DGGE analysis, detecting at least 7 different species. Vibrio vulnificus, Lactobacillus plantarum group, and Lactobacillus parafarraginis were present in samples from both cultivars; Lactobacillus sanfranciscensis and Halolactobacillus halophilus were detected only in Gordal samples, while Staphylococcus sp. was exclusively found at the onset of Manzanilla fermentations. Physicochemical data showed a typical fermentation profile while scanning electron microscopy confirmed the in situ biofilm formation on the olive epidermis. Different Bacillus, Staphylococcus and Enterococcus species, not detected during the fermentation process, were also found in the solid marine salt used by the industry for preparation of brines. Elucidation of these non-lactic acid bacteria species role during fermentation is then an appealingly challenge, particularly regarding safety issues.